Imperfective Aspects of Non-Temporal Arabic in the Translation of Ar-Raḥīqul Makhtūm to Indonesia: Discourse Semantic Analysis - Yasmin Afifah; Moh. Masrukhi (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2023)
Imperfective aspects of Arabic are often expressed with imperfect verbs or fiil mudhari, declaring past, present, and future tenses accompanied by lexical additions. This paper aims to reveal the imperfect aspect of non-temporal tenses in translating the book Ar Raḥīqul Makhtūm. The theory used to mark the non-temporal narration by Hooper (1979) and developed by Hoed (1992). This research uses a descriptive qualitative approach. The data taken could be better in translating the book Ar-Raḥīqul Makhtūm. The novelty of this study lies in the non-temporal epoch of Arabic, which previous researchers have never studied. The non-temporal clause consists of precedence and background in declarative clauses. The results of this study are that imperfective aspects are often composed using imperfect verbs, which act as a background, and perfect verbs act as a foreground in Arabic. Imperfective aspects are expressed, both through verbs and nouns. These sentences produce single or multiple translations by paying attention to the realization of pronouns that produce complex sentences commensurate with the translation results to understand the discourse.